Determinan Kinerja Pegawai dalam Reformasi Birokrasi: Peran Kepemimpinan Transformasional, Budaya Organisasi, dan Manajemen Talenta - Fatmawati Fatmawati; Nurchayati Nurchayati; Endang Swastuti; Sri Suprapti (Jesya, 2026)
The increasingly complex dynamics of government organizations present significant challenges in managing human resources to enhance employee performance. Leadership, organizational culture, and talent management play crucial roles in achieving organizational effectiveness, particularly in the education and culture sector. This study examines how transformational leadership, organizational culture, and talent management influence employee performance at the Department of Education and Culture of Batang Regency within the context of bureaucratic reform. This research employs a quantitative approach, with the population consisting of all employees of the institution. A sample of 96 employees in 2025 was selected using purposive sampling techniques. Data were collected through questionnaires and analyzed using multiple regression analysis. The results indicate that transformational leadership has a positive and significant effect on employee performance. Organizational culture also has a positive and significant effect on employee performance. Furthermore, talent management exerts a positive and significant influence on employee performance. These findings suggest that better implementation of transformational leadership, a stronger organizational culture, and more effective talent management lead to improved employee performance. This study underscores the importance of enhancing leadership quality, strengthening organizational culture, and optimizing talent management to promote improved employee performance in the government sector.